Busy Stores and Demanding Customers: How Do They Affect the Display of Positive Emotion? - Rafaeli, Anat; Sutton, Robert I. (Academy of Management Journal, 1990)
This study replicates and extends our prior research on expressed emotions. We propose that the levels of a store's busyness and customer demand influence the emotions service employees express during transactions with customers. The busyness surrounding a transaction and the level of demand the transaction places on an employee are cues that provoke inner feelings and provide information about which emotions the employee can best use to gain control over the transaction. We tested three hypotheses reflecting this conceptual perspective using structured observations of 194 transactions between cashiers and customers in five supermarkets. Findings support the hypotheses that busyness is negatively related to cashiers' displayed positive emotion and that customer demand is positively related to displayed positive emotion. Findings do not support the hypothesis that the positive relationship between demand and positive emotion is weaker in busy stores than in slow stores.